20 Recipient related predictors of mortality after heart transplantation: results from a contemporary irish national cohort. (7th October 2015) - Ryan, N; Mahon, N; McCarty, J; Nokle, L; Parlon, B; Egan, J; O'Neill, J; McGuinness, J; Barrett, M; Eisaka, A
Abstract : Background: Orthotopic Heart Transplantation (OHT) remains the optimal therapy for advanced symptomatic heart failure unresponsive to other interventions in appropriately selected patients. Assessing outcomes of OHT, including mortality and its predictors, is of importance, not only to the transplant centre but also to the referring heart failure services, to assist in optimising and aligning expectations. Alongside advances in post-transplant care, older and more complex patients are being listed for OHT, therefore it is important to validate survival in a contemporary cohort. Objectives: We sought to assess the outcome following OHT in our contemporary cohort and to identify recipient risk factors of poor outcome. Diabetes, renal disease and advanced age at transplantation are all identified in the literature as predictors of poor outcomes post transplantation. Methods: A systematic analysis of all patients (n = 100) transplanted in the eleven-year period 2004–2013 attending follow up in the Irish post transplant clinic was performed. Our analysis included both patients transplanted in the Irish transplant programme and young adults transitioned to the Irish programme following paediatric transplantation in the UK. Review of inpatient and outpatient records together with laboratory data allowed completion of a standardised set of data elements for each patient. Survival was determined with reference to the clinical records. Statistical analysis was carried out using SPSS. Survival curves were generated and the log-rank scale was used to compare survival among different groups. Results: Baseline characteristics for our population are shown in Table 1 . The Kaplan-Meier Survival curve for the study population is shown Figure 1 . One-year survival was 85% with death occurring in 25 patients during the study period, all surviving patients remained free of re-transplantation at the end of the study period. Univariate determinants of increased mortality included female gender and CKD class at transplantation, but not age at transplantation or diabetes. Early deaths occurred more frequently in the ischaemic cohort, however they had a superior long-term survival (p 0.018). Conclusions: Our survival rates are in keeping with the international data published by the International Society for Heart and Lung Transplantation. In our data only renal impairment and female gender were identified as predictors of poor outcome perhaps due to the small numbers in our cohort.